Analysis of Rhodamin B Levels in Lipbalms Sold Online Using Uv-Vis Spectrophotometry - Cahya, Cucu Arum Dwi; Saragih, Agustinus; Br Sinaga, Hana Lorenta (Jurnal FARMASIMED (JFM), 2024)
A frequent cosmetic preparation for moisturizing and shielding dry lips is lip balm. The textile industry uses a synthetic dye called rhodamine B. Because rhodamine B is a synthetic dye having carcinogenic qualities that can encourage the formation of cancer cells if used repeatedly, the Indonesian Food and Drug Administration (BPOM) forbids its usage as a cosmetic colorant. The purpose of the study is to ascertain, both qualitatively and quantitatively, if five distinct lip balm brands sold online contain the dangerous synthetic pigment Rhodamine B. The study was conducted quantitatively using UV Vis spectophotometry and qualitatively using the Thin Layer Chromatography (TLC) test and color response test with the reagents used, 10% NaOH. One of the five samples (sample B) tested positive for Rhodamine B according to the color response and TLC tests. With an Rf value of 0.91, which is near the typical Rhodamine B Rf value of 0.96, this was demonstrated by a color shift to red-orange upon the addition of 10% NaOH. Visual inspection of Sample B revealed a pink area as well. Rhodamine B was not detected in samples A, C, D, or E.Sample B had an average Rhodamine B content of 3,2281 mg/g.